2011
DOI: 10.1158/1078-0432.ccr-10-1980
|View full text |Cite
|
Sign up to set email alerts
|

High Impact of Oatp1a/1b Transporters on In Vivo Disposition of the Hydrophobic Anticancer Drug Paclitaxel

Abstract: Purpose: Organic anion-transporting polypeptides (OATP) mediate the cellular uptake of a broad range of drugs. The hydrophobic anticancer drug, paclitaxel (PTX), was recently identified as a substrate for OATP1B3 in vitro. We investigated the role of Oatp1a/1b transporters in the pharmacokinetics of PTX in vivo, as well as their impact at different dose levels of PTX and methotrexate (MTX).Experimental Design: Recently generated Slco1a/1b À/À (lacking all Oatp1a/1b transporters) and wildtype mice were intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 32 publications
7
38
0
Order By: Relevance
“…In particular, we previously reported that paclitaxel and docetaxel are transported substrates of human OATP1B1 (SLCO1B1) and OATP1B3 (SLCO1B3) (14)(15)(16)(17), as well as the single functional homolog OATP1B2 (Slco1b2) in mice (18) and rats (18,29). These findings have been independently verified (30)(31)(32)(33)(34), and are consistent with in vitro studies that have identified paclitaxel as a potent inhibitor of OATP1B1-(35, 36) and OATP1B3-mediated transport (35,37,38). However, none of the other known 9 human OATPs or other rodent OATPs are capable of transporting paclitaxel (39), and similar results have been obtained with docetaxel (40).…”
Section: Oatp1b2 As a Putative Paclitaxel Transporter In Mouse Neuronsmentioning
confidence: 73%
“…In particular, we previously reported that paclitaxel and docetaxel are transported substrates of human OATP1B1 (SLCO1B1) and OATP1B3 (SLCO1B3) (14)(15)(16)(17), as well as the single functional homolog OATP1B2 (Slco1b2) in mice (18) and rats (18,29). These findings have been independently verified (30)(31)(32)(33)(34), and are consistent with in vitro studies that have identified paclitaxel as a potent inhibitor of OATP1B1-(35, 36) and OATP1B3-mediated transport (35,37,38). However, none of the other known 9 human OATPs or other rodent OATPs are capable of transporting paclitaxel (39), and similar results have been obtained with docetaxel (40).…”
Section: Oatp1b2 As a Putative Paclitaxel Transporter In Mouse Neuronsmentioning
confidence: 73%
“…Given the large overlap in tissue distribution and substrate specificity within the OATP1 family, another transgenic mouse model deficient for all five established Slco1a and Slco1b genes (Slco1a/1b −/− mice) has also been developed (54). These mice lacking Oatp1a1, Oatp1a4, Oatp1a5, Oatp1a6, and Oatp1b2 displayed drastically reduced hepatic uptake of methotrexate, fexofenadine, and paclitaxel and subsequently increased systemic exposure for all of these drugs (54,55).…”
Section: Animal Models To Investigate the Role Of Oatps In The Disposmentioning
confidence: 99%
“…Briefly, in the absence of Oatp1a/1b transporters, plasma levels of methotrexate and paclitaxel were markedly increased, whereas hepatic uptake and biliary excretion were significantly decreased (15,16). Methotrexate and paclitaxel are structurally diverse anticancer drugs, with methotrexate being a charged organic anion and paclitaxel a highly hydrophobic drug.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations, we have now generated humanized OATP1B1, OATP1B3, and OATP1A2 transgenic mice (Slco1a/1b À/À ;1B1 tg , Slco1a/1b À/À ;1B3 tg , and Slco1a/ 1b À/À ;1A2 tg , respectively) with liver-specific expression of each of the transgenic cDNAs in an Oatp1a/1b knockout background. Transgenic expression in liver parenchyme cells (hepatocytes) was chosen in view of the exclusive liver expression and basolateral (sinusoidal) hepatocyte localization of OATP1B1 and OATP1B3 in humans, and the previously established prominent pharmacokinetic role of mouse Oatp1a/1b transporters in the liver (15,16). Preliminary partial physiologic analysis of 2 of these 3 mouse models has shown the importance of human OATP1B1 and OATP1B3 in bilirubin detoxification by the liver.…”
Section: Introductionmentioning
confidence: 99%